Patterns and Reasons for Junk Food Consumption among Young Adults: A Mixed Methods Study from a Medical College in South India - Poonam Ramesh Naik; S. Vineetha; Nagendra Navya (Archives of Medicine and Health Sciences)
Background and Aim: Food item that has little nutritive value, high fat, and sugar content with little to no fiber content is labeled as junk food. The objective of the study is to assess the patterns of consumption of junk food among young adults and to explore the reasons for junk food consumption among young adults. Materials and Methods: Mixed method study consisting of quantitative phase involving interviews with 116 students from a Medical College using a semi-structured, validated questionnaire circulated through Google Forms followed by an depth interview of 10 participants for qualitative phase. Results: In the study, it was observed that (62.2%) eat junk food during snack time. Students staying with friends (35.3%) consumed more junk food compared to the ones staying with family (13.8%). The most common reasons for junk food consumption were its good taste (77.6%) and (68.1%) convenience. It is observed that maximum consumption of junk food is seen when meeting their friends (70.7%) and on special occasions (61.2%). French fries (69.8%) were the most common junk food consumed although (76.7%) felt that junk food is unhealthy. The qualitative interview also supported the findings that the most common reasons for junk food consumption were craving, inexpensive, taste, and poor taste of hostel food. Conclusion: The above study concluded that majority of the students consumed junk food when staying with friends and due to its good taste and convenience and to spend quality time with their family and on special occasions. Participants were aware that junk food is unhealthy but consume it because it is delicious while being pocket friendly.